Error estimates for Hermite and even-tempered Gaussian approximations in quantum chemistry - Bachmayr, Markus; Chen, Huajie; Schneider, Reinhold (Numerische Mathematik, 2014)
Atomic-like basis functions provide a natural, physically motivated description of electronic states, among which Gaussian-type orbitals are the most widely used basis functions in molecular simulations. This paper aims at developing a systematic analysis of numerical approximations based on linear combinations of Gaussian-type orbitals. We derive a priori error estimates for Hermite-type Gaussian bases as well as for even-tempered Gaussian bases. Numerical results are presented to support the theory.